Unfair trade in Central America : the new regulation, the GATT, and the regional integration process. - ROBERT, Carolyn (1997)
Examines the new Central American Regulation on Unfair Trade in the context of the implementation of the Uruguay Round Agreement in light of regional economic integration and liberalization.